The Global Landscape of the Burden of Depressive Symptoms/Major Depression in Individuals Living With HIV/AIDs and Its Effect on Antiretroviral Medication Adherence: An Umbrella Review - Necho, Mogesie; Zenebe, Yosef; Tiruneh, Chalachew; Ayano, Getinet; Yimam, Bethlehem (Frontiers in Psychiatry, 2022)
Background: People living with HIV/AIDS have a higher rate of depression/depressive symptoms and this highly affects antiretroviral medication adherence. Therefore, much stronger evidence weighing the burden of depressive symptoms/major depression is warranted. Methods: We investigated PubMed, Scopus, Psych-Info, Embase databases for systematic review studies. A PRISMA flow diagram was used to show the search process. We also used the Assessment of Multiple Systematic Reviews (AMSTAR) checklist scores. A narrative review and statistical pooling were accompanied to compute the pooled effect size of outcome variables. Results: Overall, 8 systematic review studies addressing 265 primary studies, 4 systematic review studies addressing 48 primary studies, and six systematic review studies addressing 442 primary studies were included for depressive symptoms, major depression, and their effect on medication non-adherence respectively. Globally, the average depressive symptoms prevalence using the random effect model was 34.17% (24.97, 43.37). In addition, the average prevalence of major depressive disorder was obtained to be 13.42% (10.53, 16.31). All of the 6 included systematic review studies reported a negative association between depressive symptoms and antiretroviral medication non-adherence. The pooled odds ratio of antiretroviral medication adherence among patients with depressive symptoms was 0.54 (0.36, 0.72) (I2 = 0.0%, p = 0.487). Conclusions: Globally, the prevalence of depressive symptoms and major depression was high. There existed a high degree of association between depressive symptoms and antiretroviral medication non-adherence. So, focused intervention modalities should be developed and implemented.